Fire as a Selection Agent for the Dissemination of Invasive Species: Case Study on the Evolution of Forest Coverage - Nunes, Leonel (2021)
Climate change has enhanced the occurrence of rural fires, since changes in the hydrologicalcycle have led to the occurrence of increasingly long and frequent periods of drought. This recurrenceof rural fires in Portugal, in turn, has led to the successive elimination of vast areas traditionallyoccupied by native species or species of economic interest, which are being successively replaced bynew species with invasive behavior. Among these,Acacia dealbatastands out for its dispersion capacityand for the area it has already occupied. In the present work, which reviews the evolution of forestcover over the last 18,000 years in the Serra da Estrela Natural Park, we intend to demonstrate thatfire acts as a species selection agent and that it enhances the development of heliophile and pyrophytespecies. For this purpose, an area of the municipality of Seia was selected, more specifically Casal doRei, where the development ofAcacia dealbataforests is monitored. In the end, it was concluded that,in fact, by analyzing the ages of the specimens present in these populations, fire acts as a selectionagent by freeing up the space previously occupied by other species, opening the way for the growthof heliophiles and pyrophytes invasive species while enhancing their germination.